Garfield syndrome: correlation between organizational hypocrisy, organizational cynicism and distrust in organizational context - Garrett, Filipe Claudino Leão Fernandes (2018)
Organizational hypocrisy, sensu Brunsson, has emerged in literature separately from akin constructs, namely organizational cynicism and distrust. Likewise, these are almost invariably treated as negative for both people and organizations. This study intends both to treat these constructs conjointly, as they may operate concomitantly, and question its unconditional negative nature, following a "brunssonian" perspective. For this purpose, we departed from a sample of 289 workers to test: 1) the aggregability of these constructs into a single 2nd order one, i.e. a syndrome; 2) how they differentially relate with lack of reciprocity and psychological contract breach; and 3) the extent of its comparative explanative power on EVLN behavioral strategies. Findings suggest that organizational hypocrisy, cynicism and distrust should be treated as a 2nd order construct, as they showed better fit indices in a confirmatory factor analysis. Likewise, when taken as a syndrome, they allow for more robust models both when treated as criterion variable and when treated as predictor of EVLN behavioral strategies, always explaining more variance.